Elementary statistics - Johnson, Robert (Boston, Massachusetts : PWS-KENT Publishing Company, 1988)
The primary objective of Elementary statistics, is to present a truly readable introduction to statistics - one that will motivate students by presenting statistics in a context that relates to their personal experiences and that is organized to promote learning in a context that relates to their personal experiences and that is organized to promote learning and understanding.
Chapter 1. Statistics -- 2. Descriptive analysis and presentation of single-variable data -- 3. Descriptive analysis and presentation of bivariate data -- 4. Probability -- 5. Probability distributions -- 6. Normal probability distribution -- 7. Sample variability -- 8. Introduction to statistical inferences -- 9. Inferences involving one population -- 10. Inferences involving two populations -- 11. Additional applications of chi-square - 12. Analysis of variance -- 13. Linear correlation and regression analysis -- 14. Elements if nonparametric systems.
Includes bibliographical references and index.
Keywords: STATISTICS